Awareness of Gluten-Free Diet among the General Public in Saudi Arabia - Alhusseini, Noara; BAJABER, Maryam Omar; SHABI, Shama Mohammed; BIN SAEEDU, Suaad Salah; ALJEJAKLI, Ragad Abdul Hak; ALSHARIMI, Ebtehal Mohammed; ALABADI-BIERMAN, Alaa (Nutrición Clínica y Dietética Hospitalaria, 2023)
Introduction: Gluten is the combination of gliadin and glutenin within a fraction of wheat. Its fraction is used in food processing because of its unique structure-building attributes. The gluten in wheat flour forms a three-dimensional protein network when mixed and hydrated properly. Even those without a diagnosis of an illness linked to gluten are beginning to follow a GFD. Methodology: This study aimed to examine the knowledge and use of the gluten-free diet among the general population of Saudi Arabia. This cross-sectional study included participants 18 years and older. Frequencies and percentages were used for descriptive data. Results: A total of 793 were included in the study. More than half of the participants knew what gluten and gluten-free diet are. Females demonstrated a greater awareness of gluten-free diet and their use (%). Other questions on the prevalence of gluten-free diet use showed that 5% follow it rigorously, while 10.3% follow it with lapses. Conclusion: The majority of the respondents were aware of the gluten diet; mostly, the gluten-free diet was followed due to health-related lifestyles. Future research on a broader scale in SA is highly needed to better understand the Saudi population.